UPAYA PENGEMBANGAN TARI MANCAK PADANG DI NAGARI PAUH IX KECAMATAN KURANJI KOTA PADANG - Fani Putri Anggraini; Herlinda Mansyur; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2014)
Abstract This article was intented to reveal the endeavors to promote Mancak Padang dance in Nagari Pauh IX Kecamatan Kuranji Kota Padang . This was a qualitative research wich used descriptive method. The data was collected through observation, interview, dokumentation and library study. The result of the research showed that the efforts done to develop the dance could be seen from the number of people perfoemed it by increasing the number of the dancers, training the young generation about Mancak Padang dance. The first training was conducted on November 30th, 2013 in which the number of the dancers were 10 people. The second one was carried out on Desember 7th, 2013 in which the number of the number of the dancers were 11, and in the third trining wich was done on December 14,15 dancers were trained. Kata kunci:Upaya, Pengembangan, tari, Mancak Padang.